Perampanel for adjunctive treatment of partial‐onset seizures: A pooled dose–response analysis of phase III studies. Issue 3 (7th March 2014) - Kramer, Lynn D.; Satlin, Andrew; Krauss, Gregory L.; French, Jacqueline; Perucca, Emilio; Ben‐Menachem, Elinor; Kwan, Patrick; Shih, Jerry J.; Laurenza, Antonio; Yang, Haichen; Zhu, Jin; Squillacote, David
Summary Objective To better understand the relationship between efficacy and perampanel dose, integrated actual (last) dose data from three phase III trials and an extension study (blinded Conversion Period; open‐label Maintenance Period) were analyzed. Methods Seizure frequency data were analyzed in patients who were randomized to and completed the 13‐week Maintenance Period of the phase III studies on perampanel 8 mg, and who received an actual (last) dose of 12 mg during (1) the extension 16‐week blinded Conversion Period or (2) weeks 1–13 of the extension Maintenance Period. Due to a treatment‐by‐region interaction (p = 0.042), analyses excluded patients from the Latin America region (n = 162/1, 480; 10.9% of the treated cohort). Results Of 372 patients randomized to 8 mg in the phase III studies, 273 completed the Maintenance Period at 8 mg and 267 entered the extension study. In patients who then had an actual (last) dose of 12 mg during the extension blinded Conversion Period (n = 217), median percent change in seizure frequency per 28 days improved from −32.4% (8 mg, phase III Maintenance Period) to −44.2% (12 mg, extension blinded Conversion Period); 50% responder rates increased slightly from 37.3% to 42.9%. In patients who completed the phase III studies on 8 mg and had an actual (last) dose of 12 mg during weeks 1–13 of the extension Maintenance Period (n = 181), median percent change in seizure frequency per 28 days improved from −34.1% (phase III Maintenance Period) to −46.0% (weeks 1–13 extension Maintenance Period); 50% responder rates were 39.2% and 46.4%. Seizure control remained substantially unchanged in patients who completed the phase III studies at 12 mg and continued on that dose during the extension. Significance Increasing perampanel dose from 8 to 12 mg can produce additional benefits in seizure control in at least some patients who tolerate the higher dose.